Financial modelling, risk management of energy instruments and the role of cryptocurrencies - Toan Luu Duc Huynh; Muhammad Shahbaz; Muhammad Ali Nasir; Subhan Ullah (Annals of Operations Research, 2020)
This paper empirically investigates whether cryptocurrencies might have a useful role in financial modelling and risk management in the energy markets. To do so, the causal relationship between movements on the energy markets (specifically the price of crude oil) and the value of cryptocurrencies is analysed by drawing on daily data from April 2013 to April 2019. We find that shocks to the US and European crude oil indices are strongly connected to the movements of most cryptocurrencies. Applying a non-parametric statistic, Transferring Entropy (an econophysics technique measuring information flow), we find that some cryptocurrencies (XEM, DOGE, VTC, XLM, USDT, XRP) can be used for hedging and portfolio diversification. Furthermore, the results reveal that the European crude oil index is a source of shocks on the cryptocurrency market while the US oil index appears to be a receiver of shocks.
Keywords: O31; G18; O32; O33; 000; Energy markets; Risk management; Crude oil; Cryptocurrency; Transfer entropy; Financial instruments